Single Metal Atom Photocatalysis. Issue 9 (21st January 2019) - Wang, Bin; Cai, Hairui; Shen, Shaohua
Abstract: Photocatalysis suffers from rapid recombination of photoexcited charge carriers and limited active sites for the catalytic reactions, resulting in unsatisfactory performances that are far from practical application. Single metal atom catalysts not only increase the number of active sites due to the maximum atom‐utilization efficiency, but also enhance the intrinsic activity of each active site because of their unique geometric and electronic features. Furthermore, single metal atom catalysts provide a platform for photocatalysis research on the atomic level. This review discusses the unique characteristics, including geometric and electronic properties, of single metal atom catalysts, summarizes their synthesis strategies, and reviews their most recent development in photocatalysis. Finally, the challenges of single metal catalysts for both fundamental research and practical application are highlighted. Abstract : Single metal atom catalysts bridge the gap between heterocatalysis and homocatalysis, and provide a platform for photocatalysis research on the atomic level. Their geometric and electronic properties, synthesis strategies, and the most recent developments in photocatalysis are reviewed. The challenges of single metal atom catalysts for both fundamental research and practical application are also discussed for future investigations.